PENGARUH METODE PEMBAYARAN CASH ON DELIVERY PADA APLIKASI SHOPEE TERHADAP DAYA BELI KONSUMEN : Studi Kasus Pada Mahasiswa UINSU - Mhd Fathur Rizqi Zuhada Hsb; Zein Zahara Br Surbakti; Ema Khairani; Purnama Ramadani Silalahi (Gapenas Publisher, 2023)
COD is a payment method that is made directly on the spot after the order from the courier is received by the buyer. The method used in this research is a quantitative method in the form of a survey. Data analysis techniques were carried out by utilizing descriptive statistics, using a percentage formula. The results of this study indicate that the Cash On Delivery (COD) payment method affects consumer purchasing power